Método para seleção de fornecedores internacionais a partir de análise multicriterial - Cardoso, Caroline (My University, 2019)
Supplier selection process is extremely important in the company's strategic management, since it implies directly in the quality of the product and also in the financial management of the company. Thus, as organizations have become increasingly demanding about choosing their suppliers, they create a serie of evaluation criteria that aim to reduce the possibility of errors in partnerships and also assist in the purchasing process. In view of this, the present study proposes na internacional suppliers selection method for input purchases, that it?s based on the existing AHP, linear weighting and TCO selection methods in the literature. For the elaboration of this study, a bibliometric analysis was performed, allied to a bibliographic review, which have considered the main national suppliers selection methods, the criteria assigned to these selection methods and other criteria mentioned by the several authors that discuss about the theme. In addition, also were differentiated the selection processes of national suppliers from international suppliers, also approaching supply chain management.(sic)
O processo de seleção de fornecedores é de extrema importância na gestão estratégica da empresa, uma vez que implica diretamente na qualidade do produto ofertado e também no gerenciamento financeiro da companhia. Com isso, as organizações têm se tornado cada vez mais exigentes na escolha de seus fornecedores, criando uma série de critérios avaliativos que visam a redução da possiblidade de erro nas parcerias e auxiliam no processo decisório de compra. Frente a isso, o presente estudo propôs um método de seleção de fornecedores internacionais de insumos, baseado nos métodos AHP, ponderação linear e TCO já existentes na literatura. Para a elaboração desse estudo foi realizada uma análise bibliométrica, aliada à uma revisão bibliográfica, em que foram considerados os principais métodos de seleção de fornecedores nacionais, os critérios atribuídos a eles e os demais critérios citados pelos diversos autores que discorrem sobre o tema. Além disso, também foram diferenciados os processos de seleção de fornecedores nacionais dos fornecedores internacionais, abordando também a gestão da cadeia de suprimentos.(sic)
Keywords: Cadeia de suprimentos; Planejamento estratégico